2014
DOI: 10.1021/jp506156e
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Adsorption on TiO2 Anatase Surfaces

Abstract: The dopamine-TiO 2 system shows a specific spectroscopic response, Surface Enhanced Raman Scattering (SERS), whose mechanism is still unknown. In this study the goal is to reveal the key role of the molecule-nanoparticle interface in the electronic structure by means of ab initio modeling. The dopamine adsorption energy on anatase surfaces is computed and related to changes in the electronic structure. Two features are observed:The appearance of a state in the material band gap, and charge transfer between mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 37 publications
2
38
1
Order By: Relevance
“…52,53 Urdaneta et al investigated the adsorption of dopamine in a low coverage regime, by considering uniquely a bidentate configuration on different low index anatase surfaces. 54…”
Section: Introductionmentioning
confidence: 99%
“…52,53 Urdaneta et al investigated the adsorption of dopamine in a low coverage regime, by considering uniquely a bidentate configuration on different low index anatase surfaces. 54…”
Section: Introductionmentioning
confidence: 99%
“…16 Second, theoretical calculations have revealed the possible interaction between TiO 2 and dopamine (DA). 17,18 Inspired by the unique characteristic of the core-shell structures, in which a direct contact between TiO 2 and DA can be guaranteed and maximized through a synthesis control, we therefore managed to coat the TiO 2 cores by using PDA nanoshells. Briefly, TiO 2 @PDA was formed by a seeded-growth method with anatase TiO 2 nanoparticles as the core material, which were then encapsulated by PDA through the oxidative self-polymerization of dopamine (Fig.…”
mentioning
confidence: 99%
“…Recently, facet engineering has been used for improving the SERS behavior of plasmon-free materials [69,70]. For example, compared with much less affinity for the {101} TiO 2 , Urdaneta et al reported a selective adsorption of dopamine (DA) on the {001} and {100} terminations, which was consistent with the CT associated to the SERS effect [182]. Guo et al from DA molecules adsorbed on a symmetric prickly {201} TiO 2 , which is three orders of magnitude higher than that on asymmetric {001}, {101}, and {100} TiO 2 (Fig.…”
Section: Facet Engineeringmentioning
confidence: 96%